OARSI Clinical Trials Recommendations: An abbreviated regulatory guide to the clinical requirements for development of therapeutics in osteoarthritis. Issue 5 (May 2015) - Simon, L.S.
Summary: In this brief abbreviated review of regulatory issues regarding the development of drugs and or devices for the treatment of osteoarthritis (OA), the steps that are expected by both the Food and Drug Administration (FDA) and the European Medicines Agency (EMA) are discussed.